(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
Today, the rapid global development of digital banks demonstrates the ongoing transformation of the banking system and indicates that its future is closely linked to the activities of fintech companies. The growing number of digital banks and the speed and convenience of the services they offer provide them with a significant competitive advantage over traditional banks. As a result, conventional banks are actively investing in the expansion of digital products and services, as well as in cooperation with fintech companies in order to deliver innovative solutions to their customers. Overall, the future development of the banking sector remains directly dependent on the progress of fintech companies that introduce financial innovations and advanced technologies.